Correlational studies on insulin resistance and leptin gene polymorphisms in peritoneal dialysis patients - Cao, Liou (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): The aim of the study was to investigate the relationship between insulin resistance (IR) and leptin (LEP) gene polymorphisms in peritoneal dialysis (PD) patients. MATERIALS AND METHODS: From July 1, 2011 to August 1, 2011, patients who received chronic PD were chosen and divided into three groups (DM, high HOMR-IR, and low HOMR-IR). Two PCR products of LEP were sequenced and aligned and the distribution of polymorphisms was analyzed using χ(2) analysis. In addition, serum leptin level, PD conditions, and biochemical parameters according to different genotype of G-2548A and A19G were statistically analyzed (P-value<0.05). The relationship between LEP gene polymorphisms and prognosis was explored. RESULTS: Totally 157 patients with average age of 55±15 years old were chosen. Distribution of genotype frequencies was complied with Hardy-Weinberg equilibrium. Leptin level and BMI (body mass index) of the GG genotype of G-2548A were higher than that of GA or AA. The fasting glucose, cholesterol, etc. of AA genotype were lower, and the nPCR was higher than the two other genotypes. Serum leptin level and BMI of AA genotype of A19G was higher than GA and GG genotypes; meanwhile, fasting blood glucose of that genotypes was the highest. In addition, survival rate of AA group of A19G was very low. CONCLUSION: The G-2548A and A19G polymorphisms were correlated with serum leptin level and IR. Leptin A19G polymorphism may be prognostic for PD patients. This study may facilitate early intervention for IR in PD patients.